Platinum-carbon catalyst, preparation method and application thereof, and hydrogen fuel cell

By using complex reducing agent to control the exposed crystal surface of platinum particles under weak alkaline conditions, the problem of insufficient catalytic activity and stability of existing platinum carbon catalysts is solved, efficient catalytic activity and dispersion are achieved, and the performance of fuel cells is improved.

CN116072898BActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111275065.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-29
Publication Date
2025-03-11
Estimated Expiration
2041-10-29

AI Technical Summary

Technical Problem

The existing carbon-supported platinum catalysts have problems with insufficient catalytic activity and stability, especially when the platinum load is high, the dispersion is reduced and the particle agglomeration is obvious, resulting in a low utilization rate of platinum.

Method used

By using complex reducing agent under weakly alkaline conditions, the platinum precursor is reduced, and the proportion of metal platinum particles exposed to 100 crystal planes is controlled, thereby improving the catalytic activity of the catalyst. This method is simple in process and convenient in operation, and is suitable for large-scale industrial production.

Benefits of technology

The catalytic activity of the platinum carbon catalyst is significantly improved, ensuring that at least 40% of the metal platinum particles are exposed to 100 crystal planes, improving the dispersion and stability of the catalyst, and enhancing the performance of the fuel cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116072898B_ABST
    Figure CN116072898B_ABST
Patent Text Reader

Abstract

The present invention discloses a platinum-carbon catalyst and a preparation method and application thereof, and also discloses a hydrogen fuel cell using the platinum-carbon catalyst. The platinum-carbon catalyst contains a carbonaceous carrier and metal platinum particles loaded on the carbonaceous carrier, and at least 40% of the metal platinum particles expose 100 crystal faces. The preparation method comprises contacting a dispersion containing a platinum precursor and a carbonaceous material with a complex reducing agent under reduction reaction conditions, and the complex reducing agent contains formic acid and at least one selected from citric acid and / or citrate. The platinum-carbon catalyst shows improved catalytic intrinsic activity, and the preparation method has a simple process, is easy to operate, and is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a platinum-carbon catalyst and a preparation method and application thereof, and also relates to a hydrogen fuel cell using the platinum-carbon catalyst. Background Art

[0002] The sustainable development of human society will inevitably require further reduction in the use of fossil resources and vigorous research, development and promotion of efficient, clean and renewable energy technologies.

[0003] A fuel cell is a power generation device that converts the chemical energy in fuel (such as hydrogen) molecules into electrical energy with high efficiency. Its energy conversion efficiency is as high as over 60% and no pollutants are emitted. Currently, the main fuel cells include alkaline fuel cells, phosphoric acid fuel cells, methanol fuel cells, proton exchange membrane fuel cells, solid oxide fuel cells, etc. Among them, proton exchange membrane fuel cells (PEMFC) are regarded as the most promising type of fuel cell due to their advantages such as good low-temperature start-up, high power generation and rapid technological progress. The manufacturing process and cost of the membrane electrode (MEA), the core component of this type of fuel cell, are the main factors affecting its large-scale application.

[0004] The power generation efficiency of MEA in fuel cells mainly depends on the performance of the catalyst. The most common catalyst at present is carbon-supported platinum (Pt / C) catalyst. Platinum-based catalysts are expensive and have problems with insufficient catalytic activity and stability. Especially when the platinum loading is high (40% and above), the dispersion is significantly reduced, the particle agglomeration phenomenon is obvious, and the utilization rate of platinum is low.

[0005] The methods reported in the literature for improving the dispersion and catalytic activity of platinum are mainly achieved by reducing the size of platinum particles. However, when the Pt particles are too small (<2nm), the side reactions are often very serious, which restricts the performance of the catalyst.

[0006] Liquid phase reduction is one of the main methods for preparing carbon-supported platinum catalysts. This method generally uses chemical reducing agents (such as formaldehyde, formic acid, ethylene glycol, sodium borohydride, etc.) in an organic phase or an organic / water mixed system to reduce platinum salts to platinum particles at a certain temperature and immobilize them on a carbon carrier. Studies have shown that when the reducing agents are formic acid and formaldehyde, the platinum particles are smaller, while when the reducing agent is potassium borohydride, the platinum particles are significantly larger; in addition, the reduction temperature and the type of carrier will also affect the size of the platinum particles after liquid phase reduction (Huang Chengde et al., Effect of Preparation Conditions of Supported Pt / C Catalysts on Pt Crystal Size, Applied Chemistry, 2000, 17(6): 645-647).

[0007] Therefore, research and development of high-load and highly dispersed carbon-supported platinum catalysts is of great significance for further reducing the volume of MEA and improving the power density of fuel cells. Summary of the invention

[0008] An object of the present invention is to provide a platinum-carbon catalyst having improved catalytic activity.

[0009] Another object of the present invention is to provide a method for preparing a platinum-carbon catalyst, which can not only prepare a platinum-carbon catalyst with improved catalytic activity, but also has a simple process, convenient operation, and is suitable for large-scale industrial production.

[0010] According to a first aspect of the present invention, the present invention provides a platinum-carbon catalyst comprising a carbonaceous carrier and metal platinum particles supported on the carbonaceous carrier, wherein at least 40% of the metal platinum particles expose 100 crystal faces.

[0011] According to the second aspect of the present invention, the present invention provides a method for preparing a platinum-carbon catalyst, which includes contacting a dispersion with a complex reducing agent under reduction reaction conditions, wherein the dispersion contains a dispersion medium and a platinum precursor and a carbonaceous material dispersed in the dispersion medium, the pH value of the dispersion is 8-11, and the complex reducing agent contains a first component and a second component, the first component is citric acid and / or citrate, and the second component is formic acid, the molar ratio of the first component to the second component is 0.1-10:1, and the molar ratio of the complex reducing agent to the platinum precursor is 1-100:1.

[0012] According to the third aspect of the present invention, the present invention provides a platinum-carbon catalyst prepared by the method described in the second aspect of the present invention.

[0013] According to a fourth aspect of the present invention, the present invention provides use of the platinum-carbon catalyst described in the first aspect or the third aspect of the present invention in a fuel cell.

[0014] According to a fifth aspect of the present invention, the present invention provides a hydrogen fuel cell, the anode and / or cathode of the hydrogen fuel cell contains the platinum-carbon catalyst described in the first aspect or the third aspect of the present invention.

[0015] According to the platinum-carbon catalyst of the present invention, the highly active crystal faces of the metal platinum particles are exposed to a greater extent, showing improved catalytic intrinsic activity.

[0016] According to the preparation method of the platinum-carbon catalyst of the present invention, a complex reducing agent is used to reduce the platinum precursor under weak alkaline conditions, which can effectively control the type and proportion of the exposed crystal faces of the metal platinum particles, thereby effectively improving the intrinsic activity of the prepared platinum-carbon catalyst. According to the preparation method of the platinum-carbon catalyst of the present invention, when reducing, no inert atmosphere protection is required, and no high-temperature treatment and acid washing of the carbonaceous carrier are required in advance. The process is simple, the operation is convenient, and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of the exposed Pt(100) crystal plane of the platinum-carbon catalyst;

[0018] Figure 2 This is a spherical aberration electron microscope photograph of the platinum-carbon catalyst prepared in Example 1.

[0019] Figure 3 This is a transmission electron microscope photograph of the platinum-carbon catalyst prepared in Example 1.

[0020] Figure 4 This is the oxygen reduction polarization curve of the platinum-carbon catalyst prepared in Example 1 measured by oxygen reduction RDE in an oxygen-saturated 0.1 M HClO4 electrolyte.

[0021] Figure 5 This is a spherical aberration electron microscope photograph of the platinum-carbon catalyst prepared in Comparative Example 1.

[0022] Figure 6 Oxygen reduction polarization curve of the platinum carbon catalyst prepared in Comparative Example 1 measured by oxygen reduction RDE in oxygen-saturated 0.1M HClO4 electrolyte.

[0023] Figure 7 This is the oxygen reduction polarization curve of the platinum-carbon catalyst prepared in Example 2 measured by oxygen reduction RDE in an oxygen-saturated 0.1 M HClO4 electrolyte.

[0024] Figure 8 Oxygen reduction polarization curve of the platinum carbon catalyst prepared in Example 3 measured by oxygen reduction RDE in oxygen-saturated 0.1 M HClO4 electrolyte.

[0025] Fig. 9 Oxygen reduction polarization curve of the platinum carbon catalyst prepared in Example 4 measured by oxygen reduction RDE in oxygen-saturated 0.1M HClO4 electrolyte. DETAILED DESCRIPTION

[0026] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0027] According to a first aspect of the present invention, the present invention provides a platinum-carbon catalyst, which contains a carbonaceous carrier and metal platinum particles supported on the carbonaceous carrier.

[0028] According to the platinum-carbon catalyst of the present invention, at least 40% of the metal platinum particles expose 100 crystal planes. Preferably, 40-50% of the metal platinum particles expose 100 crystal planes, for example, 40-45% of the metal platinum particles expose 100 crystal planes.

[0029] In the present invention, the type of the crystal plane exposed by the metal platinum particles is characterized by using a spherical aberration corrected scanning transmission electron microscope to measure the lattice spacing (also referred to as "crystal plane spacing") of the exposed surface of the platinum particles, and the type of the exposed crystal plane is determined according to the lattice spacing, wherein, Figure 1 As shown, the crystal plane with a lattice spacing of about 0.2 nm is the Pt (100) crystal plane. In the present invention, the term "exposed surface" refers to the surface of the metal platinum particle that is not in contact with the carbonaceous support and is away from the carbonaceous support.

[0030] In the present invention, the specific test method for the proportion of metal platinum particles with 100 crystal faces exposed is: select a certain number (calculated as N1) of platinum particles with clear lattice fringes in the spherical aberration electron microscope image, and count the number of metal platinum particles whose exposed crystal faces are crystal faces with a lattice spacing of 0.2nm (calculated as N2), then the proportion of metal platinum particles with 100 crystal faces exposed is equal to N2 / N1×100%, wherein the value of N1 is greater than 100.

[0031] According to the platinum-carbon catalyst of the present invention, based on the total amount of the platinum-carbon catalyst, in terms of element, the content of platinum in the platinum-carbon catalyst can be 20-70% by weight, and the content of the carbonaceous carrier can be 30-80% by weight, and the carbonaceous carrier is calculated in terms of carbon. According to the platinum-carbon catalyst of the present invention, when the platinum content is high, a high dispersion can still be obtained, so that the metal platinum particles mainly expose 100 crystal faces. In a preferred embodiment, based on the total amount of the platinum-carbon catalyst, in terms of element, the content of platinum in the platinum-carbon catalyst is 40-60% by weight, and the content of the carbonaceous carrier is 40-60% by weight, and the carbonaceous carrier is calculated in terms of carbon.

[0032] In the present invention, the composition of the platinum-carbon catalyst is measured by inductively coupled plasma emission spectrometry (ICP method).

[0033] According to the platinum-carbon catalyst of the present invention, the carbonaceous carrier is conductive carbon black. Preferred examples of the conductive carbon black may include but are not limited to one or more of Vulcan XC-72R, Ketjen EC-300J, Ketjen EC-600J, Blackpearls 2000 and Blackpearls 3000.

[0034] The platinum-carbon catalyst according to the present invention has improved catalytic activity. The area specific activity of the platinum-carbon catalyst according to the present invention is greater than 0.4 mA·cm -2-Pt, generally 0.4-0.6 mA cm -2 In the present invention, the area specific activity of the platinum-carbon catalyst is measured by a rotating disk electrode (RDE) method.

[0035] According to the platinum-carbon catalyst of the present invention, the particle size of the metal platinum particles is uniform, generally in the range of 3-10 nm. In the present invention, the particle size of the metal platinum particles in the platinum-carbon catalyst is measured by transmission electron microscopy.

[0036] According to the second aspect of the present invention, the present invention provides a method for preparing a platinum-carbon catalyst, which includes contacting a dispersion with a complex reducing agent under reduction reaction conditions, wherein the dispersion contains a dispersion medium and a platinum precursor and a carbonaceous material dispersed in the dispersion medium.

[0037] According to the method of the present invention, the complex reducing agent contains a first component and a second component, the first component is citric acid and / or a citrate, and the second component is formic acid. Preferably, the first component is one or more of citric acid, an alkali metal salt of citric acid, and ammonium ferric citrate. More preferably, the first component is one or more of citric acid, sodium citrate, potassium citrate, and ammonium ferric citrate. According to the method of the present invention, in a particularly preferred embodiment, the first component is citric acid and the second component is formic acid.

[0038] According to the method of the present invention, the molar ratio of the first component to the second component is 0.1-10:1, for example, the molar ratio of the first component to the second component can be 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1 .8:1, 1.9:1, 2:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 2.6:1, 2.7:1, 2.8:1, 2.9:1, 3:1, 3.1:1, 3.2:1, 3.3:1, 3.4:1, 3.5:1, 3.6:1, 3.7:1, 3.8:1, 3.9:1, 4:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1 , 4.6:1, 4.7:1, 4.8:1, 4.9:1, 5:1, 5.1:1, 5.2:1, 5.3:1, 5.4:1, 5.5:1, 5.6:1, 5.7:1, 5.8:1, 5.9:1, 6:1, 6.1:1, 6.2:1, 6.3:1, 6.4:1, 6.5:1, 6.6:1, 6.7:1, 6.8:1, 6.9:1, 7:1, 7.1:1, 7.2:1, 7.3 : 1, 7.4: 1, 7.5: 1, 7.6: 1, 7.7: 1, 7.8: 1, 7.9: 1, 8: 1, 8.1: 1, 8.2: 1, 8.3: 1, 8.4: 1, 8.5: 1, 8.6: 1, 8.7: 1, 8.8: 1, 8.9: 1, 9: 1, 9.1: 1, 9.2: 1, 9.3: 1, 9.4: 1, 9.5: 1, 9.6: 1, 9.7: 1, 9.8: 1, 9.9: 1 or 10: 1. Preferably, the molar ratio of the first component to the second component is 0.5-6: 1. More preferably, the molar ratio of the first component to the second component is 1-3: 1.

[0039] According to the method of the present invention, the molar ratio of the complex reducing agent to the platinum precursor is 1-100:1. For example, the molar ratio of the complex reducing agent to the platinum precursor can be 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1 :1、19:1、20:1、21:1、22:1、23:1、24:1、25:1、26:1、27:1、28:1、29:1、30:1、31:1、32:1、33:1、34:1、35:1、36:1、37:1、38:1、39:1、40:1、41:1、42:1、43:1、44:1、45:1、4 6:1、47:1、48:1、49:1、50:1、51:1、52:1、53:1、54:1、55:1、56:1、57:1、58:1、59:1、60:1、61:1、62:1、63:1、64:1、65:1、66:1、67:1、68:1、69:1、70:1、71:1、72:1、73:1 , 74:1, 75:1, 76:1, 77:1, 78:1, 79:1, 80:1, 81:1, 82:1, 83:1, 84:1, 85:1, 86:1, 87:1, 88:1, 89:1, 90:1, 91:1, 92:1, 93:1, 94:1, 95:1, 96:1, 97:1, 98:1, 99:1, or 100:1. Preferably, the molar ratio of the complex reducing agent to the platinum precursor is 5-50:1. More preferably, the molar ratio of the complex reducing agent to the platinum precursor is 6-30:1. Further preferably, the molar ratio of the complex reducing agent to the platinum precursor is 8-20:1. Particularly preferably, the molar ratio of the complex reducing agent to the platinum precursor is 8-12:1.

[0040] According to the method of the present invention, the complex reducing agent is contacted with the dispersion under weak alkaline conditions to carry out a reduction reaction. According to the method of the present invention, the pH value of the dispersion is 8-11, for example, it can be: 8, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10, 10.1, 10.2, 10.3, 10.4, 10.5, 10.6, 10.7, 10.8, 10.9 or 11. Preferably, the pH value of the dispersion is 9-10.

[0041] According to the method of the present invention, the conditions for contacting the dispersion with the complex reducing agent are sufficient to reduce the platinum precursor in the dispersion to metallic platinum. Preferably, the dispersion is contacted with the complex reducing agent at a temperature of 40-100°C. More preferably, the dispersion is contacted with the complex reducing agent at a temperature of 50-80°C. Further preferably, the dispersion is contacted with the complex reducing agent at a temperature of 60-70°C. According to the method of the present invention, the time for the dispersion to contact the platinum precursor can be selected according to the temperature of the contact reaction. Generally, the reaction time can be 4-12 hours, preferably 4-8 hours, and more preferably 4-6 hours. According to the method of the present invention, the dispersion and the complex reducing agent can be carried out in an oxygen-containing atmosphere (such as an air atmosphere) without being carried out in an inert atmosphere (such as: an atmosphere formed by nitrogen and / or a zero group gas, specific examples of the zero group gas include but are not limited to argon and helium).

[0042] According to the method of the present invention, it is preferred that after the temperature of the dispersion is adjusted to the reduction reaction temperature, the dispersion is contacted with a complex reducing agent to further increase the number of metal platinum particles with exposed 100 crystal faces. After the temperature of the dispersion is adjusted to the reduction reaction temperature, the complex reducing agent may be added to the dispersion to perform a reduction reaction.

[0043] According to the method of the present invention, the dispersion can be prepared by conventional methods. In a preferred embodiment, the method of the present invention further comprises the step of providing the dispersion, comprising:

[0044] S1, ultrasonically dispersing a mixture containing a platinum precursor, a carbonaceous material and a dispersion medium to obtain a suspension;

[0045] S2. contacting the suspension with a pH adjuster, adjusting the pH value of the suspension to 8-11, and obtaining the dispersion.

[0046] In S1, the carbonaceous material, the platinum precursor and the dispersion medium are dispersed by ultrasound, and the carbonaceous material and the platinum precursor can be fully mixed. Preferably, the power of the ultrasound is 100-1000W, more preferably 200-800W, and further preferably 300-600W. The duration of the ultrasonic dispersion can be 0.2-0.5 hours. The present invention does not particularly limit the ultrasonic dispersion device, and the carbonaceous material, the platinum precursor and the dispersion medium can be dispersed in a common ultrasonic dispersion device.

[0047] In S2, the pH regulator can be one or more of ammonia water, sodium carbonate, potassium carbonate, ammonium carbonate, potassium hydroxide and sodium hydroxide. The pH regulator is preferably provided in the form of an aqueous solution, and the concentration of the aqueous solution can be conventionally selected without particular limitation.

[0048] According to the method of the present invention, the dispersion medium may be one or more of water and C1-C6 alcohols. The alcohol may be a combination of one or more of monohydric alcohols, dihydric alcohols and polyhydric alcohols, and the polyhydric alcohol refers to an alcohol containing three or more hydroxyl groups (-OH) in its molecular structure. According to the method of the present invention, preferred examples of the dispersion medium may include, but are not limited to, one or more of water, methanol, ethanol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol and glycerol. In a preferred embodiment, the dispersion medium is water, preferably ultrapure water. The ultrapure water refers to water with a resistivity of 18MΩ·cm (25°C).

[0049] According to the method of the present invention, the concentration of the platinum precursor in the dispersion can be conventionally selected. Generally, the concentration of the platinum precursor in the dispersion can be 1-20 g / L, preferably 5-15 g / L, and more preferably 7-12 g / L. According to the method of the present invention, the ratio between the platinum precursor and the carbonaceous material can be selected according to the amount of platinum expected to be introduced into the carbonaceous material. Generally, in the dispersion, the mass ratio of the platinum precursor to the carbonaceous material can be 0.5-7:1, preferably 1-5:1.

[0050] The method according to the present invention is not particularly limited to the type of platinum precursor, which can be a substance that can be reduced to metallic platinum under reducing conditions. Specific examples of the platinum precursor may include, but are not limited to, one or more of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, ammonium chloroplatinate, potassium hexahydroxyplatinate, sodium hexahydroxyplatinate and platinum chloride. Preferably, the platinum precursor is chloroplatinic acid.

[0051] According to the method of the present invention, the carbonaceous material is conductive carbon black. The conductive carbon black can be one or more of ordinary conductive carbon black, super conductive carbon black and special conductive carbon black. According to the method of the present invention, preferred examples of the carbonaceous material can include but are not limited to one or more of Vulcan XC-72R, Ketjen EC-300J, Ketjen EC-600J, Blackpearls2000 and Blackpearls 3000.

[0052] According to the method of the present invention, the carbonaceous material does not need to be subjected to surface modification treatment before being used to prepare the platinum-carbon catalyst, and the surface modification treatment includes but is not limited to oxidation treatment, acid washing and high-temperature treatment, etc. It can be understood by those skilled in the art that the carbonaceous material can be washed by conventional methods in the art before being used in the platinum-carbon catalyst to remove impurities and impurities attached to the surface of the platinum-carbon.

[0053] According to the method of the present invention, the reaction mixture obtained by the reduction reaction can be separated by conventional methods to obtain the platinum-carbon catalyst according to the present invention. Specifically, the solid phase material can be separated from the reaction mixture obtained by the reduction reaction by conventional separation methods, and the separated solid phase material is washed and dried in turn to obtain a platinum-carbon catalyst. Generally, the reaction mixture obtained by the reduction reaction can be subjected to solid-liquid separation by a combination of one or more of filtration, centrifugation and sedimentation to obtain a solid phase material. The drying is preferably carried out at a temperature of 80-110°C, and the duration of the drying can be 4-12 hours. The drying can be carried out at normal pressure or under conditions below atmospheric pressure.

[0054] According to the third aspect of the present invention, the present invention provides a platinum-carbon catalyst prepared by the method described in the second aspect of the present invention.

[0055] The preparation method of the platinum-carbon catalyst according to the present invention can effectively regulate the type ratio of the exposed crystal faces of the metal platinum particles in the platinum-carbon catalyst, thereby effectively improving the catalytic intrinsic activity of the platinum-carbon catalyst.

[0056] According to the platinum-carbon catalyst of the third aspect of the present invention, at least 40% of the metal platinum particles expose 100 crystal planes. Preferably, 40-50% of the metal platinum particles expose 100 crystal planes, for example, 40-45% of the metal platinum particles expose 100 crystal planes.

[0057] According to the third aspect of the present invention, the platinum-carbon catalyst has an area specific activity greater than 0.4 mA·cm -2 -Pt, generally 0.4-0.6 mA cm -2 -Pt.

[0058] According to the platinum-carbon catalyst described in the third aspect of the present invention, the particle size of the metal platinum particles is uniform, generally in the range of 3-10 nm.

[0059] According to a fourth aspect of the present invention, the present invention provides use of the platinum-carbon catalyst described in the first aspect or the third aspect of the present invention in a fuel cell.

[0060] According to a fifth aspect of the present invention, the present invention provides a hydrogen fuel cell, the anode and / or cathode of the hydrogen fuel cell contains the platinum-carbon catalyst described in the first aspect or the third aspect of the present invention.

[0061] The present invention is described in detail below with reference to the embodiments, but the scope of the present invention is not limited thereby.

[0062] In the following examples and comparative examples, transmission electron microscopy analysis was performed on a transmission electron microscope model JEM-2100 purchased from JEOL Ltd.

[0063] In the following examples and comparative examples, the types of crystal faces exposed by the metal platinum particles were characterized by using a JEM-ARM300F spherical aberration corrected scanning transmission electron microscope (hereinafter referred to as a spherical aberration electron microscope) purchased from Japan Electronics Co., Ltd., to measure the lattice spacing of the exposed surface of the platinum particles, and determine the type of the exposed crystal face according to the lattice spacing, wherein, Figure 1 As shown in FIG. 1 , the crystal plane with a lattice spacing of about 0.2 nm is the Pt (100) crystal plane. The specific test method for the proportion of metal platinum particles with exposed 100 crystal planes is as follows: a certain number (counted as N1) of platinum particles with clear lattice fringes are selected from the spherical aberration electron microscope image, and the number of metal platinum particles with exposed crystal planes having a lattice spacing of 0.2 nm is counted (counted as N2), and the proportion of metal platinum particles with exposed 100 crystal planes is equal to N2 / N1×100%, wherein the value of N1 is greater than 100.

[0064] In the following examples and comparative examples, the composition of the platinum-carbon catalyst was determined by inductively coupled plasma emission spectroscopy (ICP method).

[0065] In the following examples and comparative examples, the electrochemical activity of the platinum-carbon catalyst was tested by electrochemical voltammetry using a rotating disk electrode (RDE):

[0066] (1) The three-electrode system is a glassy carbon working electrode coated with a catalyst, a graphite counter electrode, and a saturated calomel reference electrode. The method for making the working electrode is as follows:

[0067] The platinum-carbon catalyst and ethanol were prepared into a 1 mg / mL slurry, and ultrasonic dispersion was performed for more than 30 min. 0.01 mL of the slurry was evenly coated on the surface of the glassy carbon electrode and dried naturally to obtain a working electrode.

[0068] (2) Test conditions

[0069] The electrochemically active area (ECSA) test conditions were: 0.1 M HClO4 solution, scan range 0.05-1.2 V, scan rate 50 mV / s, nitrogen saturation;

[0070] The polarization curve test conditions are: 0.1M HClO4 solution, scanning range of 0.6-1.0V, scanning rate of 10mV / s, oxygen saturation, and rotating disk electrode speed of 1600r / min.

[0071] (3) Performance parameter calculation method

[0072] Electrochemically active area (ECSA), half-wave potential (E 1 / 2 ), diffusion current density (J L ) can be read directly from the test software or polarization curve;

[0073] Kinetic current density (J K ) According to the apparent current density (J) corresponding to 0.9 V on the polarization curve 0.9V ) and diffusion current density (J L ) Press 1 / J 0.9V =1 / J K +1 / J L The formula is calculated;

[0074] The mass specific activity is expressed as J K Divide by the mass per unit area of ​​platinum on the electrode (m Pt ) was calculated, and the area specific activity was calculated by dividing the mass specific activity by ECSA.

[0075] The following examples and comparative examples involve the following conductive carbon blacks:

[0076] (1) Ketjen EC 300J conductive carbon black, purchased from Lion Corporation of Japan;

[0077] (2) Conductive carbon black of brand Vulcan XC-72R was purchased from Cabot Corporation, USA.

[0078] Examples 1-8 are used to illustrate the platinum-carbon catalyst of the present invention and its preparation method and application.

[0079] Example 1

[0080] (1) 400 mg of Vulcan XC-72R conductive carbon black was placed in 150 mL of ultrapure water, 16.2 mL of 0.19 M chloroplatinic acid aqueous solution was added, and ultrasonic dispersion (power of 200 W) was performed for 30 min to form a dispersion.

[0081] (2) While stirring, add an aqueous sodium carbonate solution to the dispersion to adjust the pH value of the dispersion to 10, then heat the dispersion to 60° C., add 5 mL of an aqueous solution of a complex reducing agent (containing 2.9 g of citric acid, with a molar ratio of citric acid:formic acid = 1:1) while stirring, and react at the same temperature in an air atmosphere for 4 h.

[0082] (3) The reaction mixture was filtered through a mobile phase filter, and the filter cake was washed with water and repeated several times until the pH of the filtrate was neutral. The washed filter cake was placed in a vacuum oven and dried at 100° C. for 12 hours to obtain a platinum-carbon catalyst. The platinum loading in the platinum-carbon catalyst was determined to be 60 wt%.

[0083] The prepared platinum-carbon catalyst was analyzed by spherical aberration electron microscopy. Figure 2 This is a spherical aberration electron microscope photo of the platinum-carbon catalyst prepared in Example 1. It is determined that the lattice spacing of the Pt particles exposed is about 0.2 nm. Figure 1As shown in the schematic diagram, the crystal plane corresponding to the lattice spacing is the Pt (100) crystal plane. Based on the measurement, it can be inferred that the number of metal platinum particles exposing the Pt (100) crystal plane in the catalyst accounts for 42%.

[0084] The TEM photo of the platinum-carbon catalyst prepared in Example 1 is as follows Figure 3 As shown, the TEM image shows that the Pt particles on the carbon support are evenly distributed, the particle size distribution is in the range of 3-10nm, and there is no obvious agglomeration phenomenon.

[0085] Figure 4 The oxygen reduction polarization curve of the platinum carbon catalyst prepared in Example 1 measured by oxygen reduction RDE in an oxygen-saturated 0.1M HClO4 electrolyte. Figure 4 It can be seen that the area specific activity of the platinum-carbon catalyst prepared in Example 1 is as high as 0.55 mA·cm -2 , which is significantly higher than the area specific activity (0.16 mA cm) of the commercial catalyst of JM Company (brand name HISPEC 9000, the mass fraction of platinum in the catalyst is 60 wt%, and the number of metal platinum particles exposed on the Pt (100) crystal surface accounts for 20-30%). -2 ), indicating that the platinum-carbon catalyst according to the present invention effectively improves the area specific activity of catalytic oxygen reduction by increasing the exposure ratio of specific crystal faces.

[0086] Comparative Example 1

[0087] A platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), citric acid was not used, and the complex reducing agent in step (2) of Example 1 was replaced by an equimolar amount of formic acid to obtain a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 59 wt%.

[0088] Figure 5 This is a spherical aberration electron microscope photo of the platinum-carbon catalyst prepared in Comparative Example 1. Figure 5 It can be seen that the platinum particles mainly expose the Pt (111) crystal plane, while the Pt (100) crystal plane accounts for a smaller proportion, among which the proportion of metal platinum particles exposing the 100 crystal plane is 25%.

[0089] Figure 6 The oxygen reduction polarization curve of the platinum-carbon catalyst prepared in Comparative Example 1 measured by oxygen reduction RDE in an oxygen-saturated 0.1M HClO4 electrolyte is shown in FIG. Figure 6 It can be seen that the area specific activity of the platinum carbon catalyst prepared in Comparative Example 1 is 0.20 mA·cm -2 , which is significantly lower than the activity of the catalyst prepared in Example 1.

[0090] Comparative Example 2

[0091] A platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), formic acid was not used, and the complex reducing agent in step (2) of Example 1 was replaced by an equimolar amount of citric acid to obtain a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 56 wt%.

[0092] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 33%. The area specific activity of the platinum-carbon catalyst was 0.23 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 .

[0093] Comparative Example 3

[0094] A platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), formic acid was replaced by an equimolar amount of formaldehyde to obtain a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 60 wt%.

[0095] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 28%. The area specific activity of the platinum-carbon catalyst was 0.21 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 .

[0096] Comparative Example 4

[0097] A platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), citric acid was replaced by an equal amount of propylene glycol to obtain a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 58 wt%.

[0098] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 30%. The area specific activity of the platinum-carbon catalyst was 0.22 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 .

[0099] Comparative Example 5

[0100] The platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), the pH value of the dispersion was adjusted to 13 to obtain a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 56 wt %.

[0101] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 35%. The area specific activity of the platinum-carbon catalyst was 0.31 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 .

[0102] Example 2

[0103] (1) 400 mg of Vulcan XC-72R conductive carbon black was placed in 150 mL of ultrapure water, 16.2 mL of 0.19 M chloroplatinic acid aqueous solution was added, and ultrasonic dispersion (power of 200 W) was performed for 30 min to form a dispersion.

[0104] (2) While stirring, add an aqueous sodium carbonate solution to the dispersion to adjust the pH of the dispersion to 10, then heat the dispersion to 60° C., add 5 mL of an aqueous solution of a complex reducing agent (containing 3.8 g of citric acid, with a molar ratio of citric acid:formic acid = 2:1) while stirring, and react at the same temperature in an air atmosphere for 4 h.

[0105] (3) The reaction mixture was filtered through a mobile phase filter, and the filter cake was washed with water and repeated several times until the pH of the filtrate was neutral. The washed filter cake was placed in a vacuum oven and dried at 100° C. for 12 hours to obtain a platinum-carbon catalyst. The platinum loading in the platinum-carbon catalyst was determined to be 60 wt%.

[0106] The prepared platinum-carbon catalyst was subjected to spherical aberration electron microscopy analysis. It was determined that the main exposed lattice spacing of the Pt particles was about 0.2nm, which was the Pt (100) crystal plane. Based on the measurement, it can be inferred that the number of metal platinum particles exposing the Pt (100) crystal plane in the catalyst accounts for 41%.

[0107] The prepared platinum-carbon catalyst was subjected to transmission electron microscopy analysis. The TEM photos showed that the Pt particles on the carbon carrier were evenly distributed, the particle size distribution was in the range of 3-8nm, and there was no obvious agglomeration phenomenon.

[0108] Figure 7 The oxygen reduction polarization curve of the platinum carbon catalyst prepared in Example 2 measured by oxygen reduction RDE in an oxygen-saturated 0.1M HClO4 electrolyte. Figure 7 It can be seen that the area specific activity of the platinum-carbon catalyst prepared in Example 2 is as high as 0.49 mA·cm -2 .

[0109] Example 3

[0110] (1) 600 mg of Vulcan XC-72R conductive carbon black was placed in 150 mL of ultrapure water, 10.8 mL of 0.19 M chloroplatinic acid aqueous solution was added, and ultrasonic dispersion (power of 200 W) was performed for 30 min to form a dispersion.

[0111] (2) While stirring, add an aqueous sodium carbonate solution to the dispersion to adjust the pH of the dispersion to 10, then heat the dispersion to 60° C., add 5 mL of an aqueous solution of a complex reducing agent (containing 3.8 g of citric acid, with a molar ratio of citric acid:formic acid = 2:1) while stirring, and react at the same temperature in an air atmosphere for 4 h.

[0112] (3) The reaction mixture was filtered through a mobile phase filter, and the filter cake was washed with water and repeated several times until the pH of the filtrate was neutral. The washed filter cake was placed in a vacuum oven and dried at 100° C. for 12 hours to obtain a platinum-carbon catalyst. The platinum loading in the platinum-carbon catalyst was determined to be 40 wt%.

[0113] The prepared platinum-carbon catalyst was subjected to spherical aberration electron microscopy analysis. It was determined that the main exposed lattice spacing of the Pt particles was about 0.2nm, which was the Pt(100) crystal plane. Based on the measurement, it can be inferred that the number of metal platinum particles exposing the Pt(100) crystal plane in the catalyst accounts for 40%.

[0114] The prepared platinum-carbon catalyst was subjected to transmission electron microscopy analysis. The TEM photos showed that the Pt particles on the carbon carrier were evenly distributed, the particle size distribution was in the range of 3-8nm, and there was no obvious agglomeration phenomenon.

[0115] Figure 8 The oxygen reduction polarization curve of the platinum carbon catalyst prepared in Example 3 measured by oxygen reduction RDE in an oxygen-saturated 0.1M HClO4 electrolyte. Figure 8 It can be seen that the area specific activity of the platinum-carbon catalyst prepared in Example 3 is as high as 0.41 mA·cm -2 .

[0116] Example 4

[0117] (1) Take 600 mg of Ketjen EC-300J conductive carbon black and place it in 150 mL of ultrapure water. Add 10.8 mL (0.19 M) of chloroplatinic acid aqueous solution and disperse it by ultrasound (power of 200 W) for 30 minutes to form a dispersion.

[0118] (2) Adding sodium carbonate aqueous solution to the dispersion with stirring to adjust the pH of the dispersion to 10, heating the dispersion to 60° C., adding 5 mL of an aqueous solution of a complex reducing agent (containing 2.9 g of citric acid, with a molar ratio of citric acid:formic acid = 1:1) with stirring, and reacting at the same temperature in an air atmosphere with stirring for 4 h.

[0119] (3) The reaction mixture was filtered through a mobile phase filter, and the filter cake was washed with water and repeated for multiple times until the pH of the filtrate was neutral. The washed filter cake was placed in a vacuum oven and dried at 100° C. for 12 hours to obtain a platinum-carbon catalyst. The platinum loading in the platinum-carbon catalyst was determined to be 40 wt%.

[0120] The prepared platinum-carbon catalyst was subjected to spherical aberration electron microscopy analysis. It was determined that the main exposed lattice spacing of the Pt particles was about 0.2nm, which was the Pt (100) crystal plane. Based on the measurement, it can be inferred that the number of metal platinum particles exposing the Pt (100) crystal plane in the catalyst accounts for 44%.

[0121] The prepared platinum-carbon catalyst was subjected to transmission electron microscopy analysis. The TEM photos showed that the Pt particles on the carbon carrier were evenly distributed, with particle sizes ranging from 3 to 10 nm, and there was no obvious agglomeration.

[0122] Fig. 9 The oxygen reduction polarization curve of the platinum carbon catalyst prepared in Example 4 measured by oxygen reduction RDE in an oxygen-saturated 0.1M HClO4 electrolyte. Fig. 9 It can be seen that the area specific activity of the platinum-carbon catalyst prepared in Example 4 is as high as 0.40 mA·cm -2 .

[0123] Example 5

[0124] The platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), the pH value of the dispersion was adjusted to 9 to obtain a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 60 wt%.

[0125] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 45%. The area specific activity of the platinum-carbon catalyst was 0.53 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 The prepared platinum-carbon catalyst was analyzed by transmission electron microscopy. The TEM photos showed that the Pt particles on the carbon carrier were evenly distributed, with a particle size distribution in the range of 3-10nm, and there was no obvious agglomeration phenomenon.

[0126] Example 6

[0127] A platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), the reaction temperature was 70° C., thereby obtaining a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 60 wt %.

[0128] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 43%. The area specific activity of the platinum-carbon catalyst was 0.51 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 The prepared platinum-carbon catalyst was analyzed by transmission electron microscopy. The TEM photos showed that the Pt particles on the carbon carrier were evenly distributed, with a particle size distribution in the range of 3-10nm, and there was no obvious agglomeration phenomenon.

[0129] Example 7

[0130] A platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), the total molar amount of the complex reducing agent remained unchanged, and the molar ratio of citric acid:formic acid was adjusted to 0.5:1, thereby obtaining a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 60 wt%.

[0131] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 42%. The area specific activity of the platinum-carbon catalyst was 0.46 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 The prepared platinum-carbon catalyst was analyzed by transmission electron microscopy. The TEM photos showed that the Pt particles on the carbon carrier were evenly distributed, with a particle size distribution in the range of 3-10nm, and there was no obvious agglomeration phenomenon.

[0132] Example 8

[0133] A platinum-carbon catalyst was prepared by the same method as in Example 1, except that in step (2), the total molar amount of the complex reducing agent remained unchanged, and the molar ratio of citric acid:formic acid was adjusted to 4:1, thereby obtaining a platinum-carbon catalyst. It was determined that the platinum loading in the platinum-carbon catalyst was 60 wt%.

[0134] Spherical aberration electron microscopy analysis showed that the proportion of exposed (100) crystal faces of platinum particles in the platinum-carbon catalyst was 41%. The area specific activity of the platinum-carbon catalyst was 0.42 mA cm-1 as determined by the oxygen reduction RDE experiment. -2 The prepared platinum-carbon catalyst was analyzed by transmission electron microscopy. The TEM photos showed that the Pt particles on the carbon carrier were evenly distributed, with a particle size distribution in the range of 3-10nm, and there was no obvious agglomeration phenomenon.

[0135] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A platinum-carbon catalyst comprising a carbonaceous carrier and metal platinum particles supported on the carbonaceous carrier, characterized in that: At least 40% of the metal platinum particles expose the (100) crystal plane, where the exposed surface refers to the surface of the metal platinum particles that is not in contact with the carbonaceous carrier and is away from the carbonaceous carrier. The test method for the proportion of the metal platinum particles that expose the (100) crystal plane is as follows: select N1 platinum particles with clear lattice fringes in the spherical aberration electron microscope image, and count the number of metal platinum particles whose exposed crystal planes are crystal planes with a lattice spacing of 0.2nm, and the number of metal platinum particles whose exposed crystal planes are crystal planes with a lattice spacing of 0.2nm is counted as N2. The proportion of the metal platinum particles that expose the (100) crystal plane is equal to N2 / N1×100%, wherein the value of N1 is greater than 100; The preparation method of the platinum-carbon catalyst comprises the following steps: contacting a dispersion with a complex reducing agent under reduction reaction conditions, wherein the dispersion contains a dispersion medium and a platinum precursor and a carbonaceous material dispersed in the dispersion medium, the pH value of the dispersion is 8-11, the complex reducing agent contains a first component and a second component, the first component is one or more of citric acid, an alkali metal salt of citric acid and ammonium ferric citrate, the second component is formic acid, the molar ratio of the first component to the second component is 0.1-10:1, and the molar ratio of the complex reducing agent to the platinum precursor is 1-100:

1.

2. The platinum-carbon catalyst according to claim 1, wherein 40-50% of the metallic platinum particles expose the (100) crystal plane.

3. The platinum-carbon catalyst according to claim 1 or 2, wherein Based on the total amount of the platinum-carbon catalyst, calculated as the element, the content of platinum in the platinum-carbon catalyst is 20-70% by weight, and the content of the carbonaceous carrier is 30-80% by weight.

4. The platinum-carbon catalyst according to claim 1 or 2, wherein Based on the total amount of the platinum-carbon catalyst, calculated as the element, the content of platinum in the platinum-carbon catalyst is 40-60% by weight, and the content of the carbonaceous carrier is 40-60% by weight.

5. The platinum-carbon catalyst according to claim 1 or 2, wherein The carbonaceous carrier is conductive carbon black.

6. The platinum-carbon catalyst according to claim 1 or 2, wherein The area specific activity of the platinum-carbon catalyst is greater than 0.4 mA cm -2 -Pt.

7. The platinum-carbon catalyst according to claim 1 or 2, wherein The area specific activity of the platinum-carbon catalyst is 0.4-0.6 mA·cm -2 -Pt.

8. The platinum-carbon catalyst according to claim 1, wherein The first component is one or more of citric acid, sodium citrate, potassium citrate and ammonium ferric citrate.

9. The platinum-carbon catalyst according to claim 1, wherein The first component is citric acid.

10. The platinum-carbon catalyst according to any one of claims 1, 8 and 9, wherein The molar ratio of the first component to the second component is 0.5-6:

1.

11. The platinum-carbon catalyst according to any one of claims 1, 8 and 9, wherein The molar ratio of the first component to the second component is 1-3:

1.

12. The platinum-carbon catalyst according to any one of claims 1, 8 and 9, wherein The molar ratio of the complex reducing agent to the platinum precursor is 5-50:

1.

13. The platinum-carbon catalyst according to any one of claims 1, 8 and 9, wherein The molar ratio of the complex reducing agent to the platinum precursor is 6-30:

1.

14. The platinum-carbon catalyst according to any one of claims 1, 8 and 9, wherein The molar ratio of the complex reducing agent to the platinum precursor is 8-12:

1.

15. The platinum-carbon catalyst according to claim 1, wherein After the temperature of the dispersion is adjusted to the reduction reaction temperature, the dispersion is contacted with a complex reducing agent.

16. The platinum-carbon catalyst according to claim 1, wherein The method further comprises the step of providing the dispersion, comprising: S1, ultrasonically dispersing a mixture containing a platinum precursor, a carbonaceous material and a dispersion medium to obtain a suspension; S2. contacting the suspension with a pH adjuster, adjusting the pH value of the suspension to 8-11, and obtaining the dispersion.

17. The platinum-carbon catalyst according to claim 16, wherein In S1, the power of the ultrasonic wave is 100-1000W, and the duration of the ultrasonic wave dispersion is 0.2-0.5 hours.

18. The platinum-carbon catalyst according to claim 16, wherein In S2, the pH adjuster is one or more of ammonia water, sodium carbonate, potassium carbonate, ammonium carbonate, potassium hydroxide and sodium hydroxide.

19. The platinum-carbon catalyst according to any one of claims 1 and 16-18, wherein The pH value of the dispersion is 9-10.

20. The platinum-carbon catalyst according to any one of claims 1 and 16-18, wherein The dispersion medium is one or more of water and C1-C6 alcohol.

21. The platinum-carbon catalyst according to any one of claims 1 and 16-18, wherein The dispersion medium is one or more of water, methanol, ethanol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol and glycerol.

22. The platinum-carbon catalyst according to any one of claims 1 and 16-18, wherein In the dispersion, the concentration of the platinum precursor is 1-20 g / L.

23. The platinum-carbon catalyst according to any one of claims 1 and 16-18, wherein In the dispersion, the mass ratio of the platinum precursor to the carbonaceous material is 0.5-7:

1.

24. The platinum-carbon catalyst according to any one of claims 1 and 16-18, wherein The platinum precursor is one or more of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, ammonium chloroplatinate, potassium hexahydroxyplatinate, sodium hexahydroxyplatinate and platinum chloride.

25. The platinum-carbon catalyst according to any one of claims 16 to 18, wherein The carbonaceous material is conductive carbon black.

26. The platinum-carbon catalyst according to claim 1, wherein The reduction reaction conditions include: reaction temperature of 40-100° C., and reaction time of 4-12 hours.

27. The platinum-carbon catalyst according to claim 26, wherein The reaction temperature is 50-80°C.

28. Use of the platinum-carbon catalyst according to any one of claims 1 to 27 in a fuel cell.

29. A hydrogen fuel cell, the anode and / or cathode of which contains the platinum-carbon catalyst according to any one of claims 1 to 27.

Citation Information

Patent Citations

  • Platinum nano cubic catalyst with no surface active agent and preparation method thereof

    CN103920490A